Pre-pandemic mental health and brain characteristics predict adolescent stress and emotions during the COVID-19 pandemic - Matthew Risner; Linfeng Hu; Catherine Stamoulis (PLoS ONE, 2025)
The COVID-19 pandemic had profound effects on developing adolescents that, to date, remain incompletely understood. Youth with preexisting mental health problems and associated brain alterations were at increased risk for higher stress and poor mental health. This study investigated impacts of adolescent pre-pandemic mental health problems and their neural correlates on stress, negative emotions and poor mental health during the first 15 months of the COVID-19 pandemic. N = 2,641 adolescents (median age = 12.0 years) from the Adolescent Brain Cognitive Development (ABCD) cohort were studied, who had pre-pandemic data on anxiety, depression, and behavioral (attention, aggression, social withdrawal, internalizing, externalizing) problems, longitudinal survey data on mental health, stress and emotions during the first 15 months following the outbreak, structural MRI, and resting-state fMRI. Data were analyzed using mixed effects mediation and moderation models. Preexisting mental health and behavioral problems predicted higher stress, negative affect and negative emotions (β = 0.09–0.21, CI=[0.03,0.32]), and lower positive affect (β = −0.21 to −0.09, CI=[−0.31,-0.01]) during the first ~6 months of the outbreak. Pre-pandemic structural characteristics of brain regions supporting social function and emotional processing (insula, superior temporal gyrus, orbitofrontal cortex, and the cerebellum) mediated some of these relationships (β = 0.10–0.15, CI=[0.01,0.24]). The organization of pre-pandemic brain circuits moderated (attenuated) associations between preexisting mental health and pandemic stress and negative emotions (β = −0.17 to −0.06, CI=[−0.27,-0.01]). Preexisting mental health problems and their structural brain correlates were risk factors for youth stress and negative emotions during the early months of the outbreak. In addition, the organization of some brain circuits was protective and attenuated the effects of preexisting mental health issues on youth responses to the pandemic’s stressors.